Solving the Problem of Finding Hypothetically Connected Objects by Means of Spatial Multi-Valued Structures - Chetverikov, G.G.; Vechirska, I.D.; Leshchynskyi, V.A. (Штучний інтелект, 2011)
In the work the basic aspects of mathematical modeling of AFP-structures as universal functional converters of spatial type on the basis of decomposition of multiple-valued structures are investigated, also there have been investigated an approach to the implementation of the linear logical transformation finding method for solving the problem of finding hypothetically connected subscribers in the automated system of complex calculations of telecommunication enterprise.